Cesarean Scar Pregnancy: Three case reports and literature review - Esther Ruiz Pérez; Cristina Álvarez Colomo; Victoria Pascual Escudero; Álvaro Sanz Díaz-Heredero; Lidia Casamayor Del Nogal; Marta Ibáñez Nieto; Sandra Canales Martínez; Jimena Bayón Pascual; Mónica Simón de la Fuente; Mónica Consuelo Horstmann Sendagorta (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Introduction: Cesarean Scar Pregnancy (CSP) is defined as an ectopic pregnancy in which the gestational sac implants on the surgical scar of a previous cesarean section or isthmocele.Despite its low incidence, the diagnosis presents a significant difficulty, and a false negative diagnosis can lead to serious complications that may require more aggressive treatments. Objective: The main objective of this study is to present three clinical cases of patients with suspected ectopic pregnancy in the cesarean scar, including a review of the current literature on this condition. Methods: The clinical case data were obtained from the patients’ medical records, including the results of the additional tests performed, as well as subsequent gynecology appointments. On the other hand, a literature review was conducted on ectopic pregnancies in the cesarean scar. Results: During ultrasound examinations of patients with a history of previous cesarean sections, special attention should be paid to identifying the implantation site of the gestational sac to rule out CSP.Due to the limited number of trials and case reports on CSP, there is no consensus on standardized treatment and management. The primary goal is to preserve patient's fertility and avoid severe complications such as massive hemorrhage or uterine rupture. Conclusions: Cesarean Scar Pregnancy (CSP) should be considered among the diagnostic options when finding a gestational sac located in atypical situations in patients with a history of cesarean section.Early diagnosis and treatment are crucial for achieving the best outcomes. A minimally invasive approach should be planned as first-line treatment in all situations where CSP is included in the differential diagnosis.